Rare Causes of Primary Adrenal Insufficiency: Genetic and Clinical Characterization of a Large Nationwide Cohort - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (ENDOCRINE SOC, 2016)
Context: Primary adrenal insufficiency (PAI) is a life-threatening condition that is often due to monogenic causes in children. Although congenital adrenal hyperplasia occurs commonly, several other important molecular causes have been reported, often with overlapping clinical and biochemical features. The relative prevalence of these conditions is not known, but making a specific diagnosis can have important implications for management. Objective: The objective of the study was to investigate the clinical and molecular genetic characteristics of a nationwide cohort of children with PAI of unknown etiology. Design: A structured questionnaire was used to evaluate clinical, biochemical, and imaging data. Genetic analysis was performed using Haloplex capture and next-generation sequencing. Patients with congenital adrenal hyperplasia, adrenoleukodystrophy, autoimmune adrenal insufficiency, or obvious syndromic PAI were excluded. Setting: The study was conducted in 19 tertiary pediatric endocrinology clinics. Patients: Ninety-five children (48 females, aged 0-18 y, eight familial) with PAI of unknown etiology participated in the study. Results: A genetic diagnosis was obtained in 77 patients (81%). The range of etiologies was as follows: MC2R (n = 25), NR0B1 (n = 12), STAR (n = 11), CYP11A1 (n = 9), MRAP (n = 9), NNT (n = 7), ABCD1 (n = 2), NR5A1 (n = 1), and AAAS (n = 1). Recurrent mutations occurred in several genes, such as c.560delT in MC2R, p.R451W in CYP11A1, and c. IVS3ds + 1delG in MRAP. Several important clinical and molecular insights emerged. Conclusion: This is the largest nationwide study of the molecular genetics of childhood PAI undertaken. Achieving a molecular diagnosis in more than 80% of children has important translational impact for counseling families, presymptomatic diagnosis, personalized treatment (eg, mineralocorticoid replacement), predicting comorbidities (eg, neurological, puberty/fertility), and targeting clinical genetic testing in the future.
Keywords: FAMILIAL GLUCOCORTICOID DEFICIENCY; STEROIDOGENIC FACTOR-I; CHAIN CLEAVAGE ENZYME; KILLER-CELL DEFICIENCY; HYPOPLASIA CONGENITA; MISSENSE MUTATIONS; ACTH RECEPTOR; DAX-1 NR0B1; FOLLOW-UP; CYP11A1